Cybersecurity skills in new graduates: a Philippine perspective - Miranda, John Paul P.; Tayag, Marlon I.; Canlas, Joel D. (International Journal of Advances in Applied Sciences, 2025)
This study investigates the key skills and competencies needed by new cybersecurity graduates in the Philippines for entry-level positions. Using a descriptive cross-sectional research design, it combines analysis of job listings from Philippine online platforms with surveys of students, teachers, and professionals. The aim is to identify required skills and areas needing improvement, highlighting the balance between technical skills and other competencies like ethical conduct, suggesting a shift away from traditional cybersecurity skills towards a more diverse skillset. Furthermore, the results revealed common agreement on the importance of communication, critical thinking, problem-solving, and adaptability skills, albeit with slight variations in their prioritization. It recommends that aspiring cybersecurity professionals develop an inclusive skill set encompassing technical knowledge, soft skills, and personal competencies, with a focus on adaptability, continuous learning, and ethics. Skills such as business acumen are considered less vital for entry-level roles, proposing a preparation strategy that aligns with the changing demands of the cybersecurity industry.